Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Karyawan KSO Peti Kemas Koja - Taufiqurrahman Baaqir; Siti Sahara (Universitas 17 Agustus 1945 Semarang, 2024)
The study aims to identify the impact resulting from training, the state of the work environment, on employee performance at KSO TPK Koja. This study wore a descriptive quantitative approach. in this study the population used was all employees of KSO TPK Koja. The information in this study is primary data obtained through the distribution of questionnaires to 37 respondents. Data analysis was tried using multiple linear regression methods using the SPSS model 25 software feature. The results prove that training has a positive and significant impact on the performance of employees produced, not only that, the work area in fact does not have an impact on employee performance.